Tau Filaments and the Development of Positron Emission Tomography Tracers - Goedert, Michel; Yamaguchi, Yoshiki; Mishra, Sushil K.; Higuchi, Makoto; Sahara, Naruhiko (Frontiers in Neurology, 2018)
A pathological pathway leading from soluble, monomeric to insoluble, filamentous Tau, is believed to underlie human Tauopathies. Cases of frontotemporal dementia are caused by dominantly inherited mutations in MAPT, the Tau gene. They show that dysfunction of Tau protein is sufficient to cause neurodegeneration and dementia. Extrapolation to the more common sporadic Tauopathies leads one to conclude that the pathological pathway is central to the development of all cases of disease, even if there are multiple reasons for Tau assembly. These findings are conceptually similar to those reported for beta-amyloid, alpha-synuclein and prion protein. Here we provide an overview of Tau filaments and their positron emission tomography ligands.